Hindering Events in Psychotherapy: A Retrospective Account from the Client’s Perspective - Burton, Lynsey (Université d'Ottawa / University of Ottawa, 2018)
This qualitative study examined retrospective client accounts of hindering experiences that occurred during therapy. In order to explore in-depth and descriptive information about client experiences of hindering events, a structured thematic analysis methodology was used that resulted in conceptual ordering (Corbin & Strauss, 2008). Data collection was conducted through face-to-face semi-structured interviews of 9 participants who had previously experienced a hindering event. Structured thematic analysis (Braun & Clarke, 2006) was used to distill themes from the collected data, where four major themes emerged from the data that were relevant to the research questions of the present study: 1) Identified Hindering Events, 2) Subjective Experience of the Event, 3) Response to the Event, 4) Handling/ Addressing the Event. Results from this study contribute to further understanding of client experiences of hindering events that occur in therapy. Implications for therapeutic organizations, therapists/ counsellors, and educators are discussed.
Keywords: hindering events; client experiences; thematic analysis